About the monograph “Collection and jewelry cassiterite” - S. V. Belov (Известия высших учебных заведений: Геология и разведка, 2021)
Specialists of the Sergo Ordzhonikidze Russian State University for Geological Prospecting (MGRI), which had been training gemologists for many years, conducted an interesting and substantial study devoted to a non-traditional use of cassiterite, a mineral known to man for millennia. The monograph2 under review discusses various aspects of the use of cassiterite, as well as its accompanying minerals, for producing jewelry, collection and ornamental materials. Given the increasing popularity of natural minerals in recent decades, there is a growth of interest among collectors and manufacturers in non-traditional semi-precious stone raw materials and their use in the jewelry industry. The world trade in this area is significant and continues to demonstrate an increasing trend. In this regard, the work of D.A. Petrochenkov devoted to jewelry and ornamental cassiterites seems to be highly relevant. For the first time in world practice, the monograph comprehensively covers questions concerning cassiterite and its application, thus contributing to popularization of cassiterite jewelry and craftsmanship and laying the foundation for a new direction in the semi-precious stone industry. The author of the monograph critically reviewed the results of previous studies on the mineral and chemical composition of cassiterite and added an extensive set of his own analytical methods. The gemological and technological characteristics of cassiterite minerals were given, along with recommendations on their rational search, use and quality improvement. In term of ecological parameters, it was shown that the content of carcinogenic and radioactive elements in jewelry cassiterites does not exceed the background values. The market conditions were described, and recommendations on the organization of mining and geological work in this sphere were presented.